Two new species of Greenisca Borchsenius, 1948 (Coccoidea Eriococcidae) from Italy and Greece (Bollettino di zoologia agraria e bachicoltura, 2024)
Two new species of Greenisca Borcbsenius (Coccoidea Eriococcidae) are described from Italy and Greece.
Keywords: Coccoidea; Eriococcidae; Greenisca alpina sp.n; Greenisca hellenica sp.n.